Poraba anksiolitikov ter hipnotikov in sedativov v Sloveniji - Fürst, Jurij (Zdravstveno varstvo, 2006)
Background: Overprescribing of some psychoactive drugs can lead to tolerance, dependence and abuse. The purpose of this paper is to address the use of anxiolytics and hypnotics/sedatives in Slovenia, to compare the situation withthat in some other countries and to highlight the most interesting findings. Methods: Data for all prescriptions of anxiolytics and hypnotics/sedatives in Slovenia during the period 2000 2004 were derived from the national Institute for Public Health and Health Insurance Institute prescription database. The results were presented as defined daily doses (DDD)per 1000 inhabitants per day. Results: Between 2000 and 2004 the use of anxiolytics decreased by 8 %, while the use of hypnotics increased by 22 %. The prevalence of use of anxiolytics is higher in women and increases with age. A significant regional variation in the use of both drug groups has been found: the difference between the region with the highest and that with the lowest frequency of use was 100 % for anxiolytics and 60 % for hypnotics/sedatives. There were even larger differences between regions concerning the use of high doses of diazepam and bromazepam, suggestive of potential abuse. Potentially excessive drug prescribing in elder patients is suggested by the observed multiple drug prescribing and simultaneous use of benzodiazepines and drugs to treat dementia. Compared to the four Scandinaviancountries, Slovenia showed a lower prevalence of hypnotic use and a higher frequency of the use of anxiolytic drugs, but a lower overall frequency of use of both groups of drugs. Conclusions: Total prevalence of anxiolytic and hypnotic use in Slovenia has been found to be lower than in Scandinavian countries, yet further efforts, prompted by wide regional variations, are needed to curb the present drug use.
Keywords: Anksiolitiki; Anti-Anxiety Agents; Bromazepam; Diazepam; drug; Drug Utilization; hipnotiki; Hipnotiki in sedativi; Hypnotics And Sedatives; poraba; predpisovanje; sedativi; zdravila; Zdravilo, uporaba